Isolation and Identification of Gut Bacteria from Mealworm (Tenebrio molitor) with Potential for Microplastic Degradation - Istiana Irbah; Marlina Kamelia; Ovi Prasetya Winandari (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2025)
Background: Plastic that accumulates in the environment over extended periods can fragment into smaller particles known as microplastics. The uncontrolled buildup of microplastics poses significant risks, including harmful health effects on living organisms and negative impacts on ecosystems. One promising sustainable solution under investigation is the use of gut bacteria from mealworm (Tenebrio molitor) for plastic biodegradation. This study aims to identify the gut bacterial species involved in degrading plastics ingested by mealworm fed with Polystyrene (PS), Polyethylene (PE), and Polyethylene Terephthalate (PET), and to evaluate the degradation rate exhibited by these bacteria. Methodology: Bacterial isolation was carried out from the gut of mealworm that were fed plastic for 30 days, using Mineral Salts Medium (MSM) as a selective medium, followed by testing the plastic degradation potential of the isolated gut bacteria. The microbial species involved were identified using the VITEX-2 Compact System. Findings: Bacteria isolated from the digestive tract of mealworm showed significant potential in degrading plastics. Pseudomonas aeruginosa was found in PS and PE treatments with degradation rates of 14.4% and 44.4%, respectively, while Aeromonas salmonicida was identified in the PET treatment with a degradation rate of 16.3%. Contribution: These findings highlight the role of mealworm gut microbes in degrading PS, PE, and PET, supporting their potential as eco-friendly biodegradation agents